PENGARUH TERAPI MUSIK TERHADAP HEMODINAMIK ANAK DENGAN LEUKEMIA - idyatul Hasanah (Unram Medical Journal, 2021)
Background: Children with leukemia undergo various series of medical procedures during treatment. This can trigger physical and psychological responses in children. The physical reaction that may occur is hemodynamic changes. Music therapy is one of the complementary therapies that can be used to overcome these physical and psychological responses. This study aims to examine the effect of music therapy on hemodynamics in children with leukemia. Methods: This is a pre-experimental study with a one-group pre-test and post-test design. All children with leukemia who met the criteria underwent treatment in the ODC room of RSUP dr. Sardjito Yogyakarta, became the respondent. Hemodynamic measurements were taken before and after a music therapy session. Data were analyzed by paired t-test. Results: There were 30 children with leukemia who met the criteria. The mean systolic blood pressure before and after music therapy were 104±12.60 and 100±14.06 (p= 0.02). The mean diastolic blood pressure before and after music therapy were 67±10.65 and 65±10.83 (p=0.30). The mean pulse rate before and after music therapy were 92±16.19 and 87±16.75 (p=0.10), respectively. Conclusion: Music therapy can significantly reduce systolic blood pressure in pediatric patients with leukemia undergoing treatment but does not affect diastolic blood pressure and pulse rate.